NILAI KEHINDUAN DALAM GEGURITAN KURUKSETRA - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Geguritan not only as entertainment alone, but can be said as a means for an author inconveying his ideas, and invites us to remember our identity and culture is very valuable. Theprocess of creating geguritan is still ongoing in society, with various main topics and actualthemes being warmed up in the community. Proven with the birth of Geguritan Yadnya RingKuruksetra. Geguritan is loaded with the value of life, especially in terms of the implementationof a yadnya based on the teachings of Hinduism. This geguritan raises the virtue of a sincereiklasan wrapped in a very simple story. The values contained therein are packaged in a structure,they can be used as guidance in people’s lives. The problem to be studied as the target of thisresearch is about the aspect of the content concerning the structure that builds the values ofGeguritan Yadnya Ring Kurusetra namely: (1) how is the structure of Geguritan Yadnya RingKurusetra? and (2) how are the values of longing in Yadnya Ring Kurusetra Geguritan. Thetheory used in this study is the structural theory of literature, especially with regard to its intrinsicstudy. Writing method used is literature study on text over script and translation GeguritanYadnya Ring Kuruksetra. In the analysis used descriptive qualitative method with combinedtechnique of deductive with inductive. Based on the study conducted, Geguritan Yadnya RingKuruksetra using the language of Bali Kepara and using a kind of pupuh, namely pupuh sinom.Behind the simplicity of the story there are very great values contained religious values (reflectedin the Three Basic Frameworks of Hinduism), which is very useful, as a guide of Hindu societyin the life of society. Values are very interesting, can be used as a very good example forHindus, especially Hindus in Bali. Especially when looking at its relevance for the community ifassociated with social phenomena that many occur in the present.Keywords: Geguritan, Literary Structure, Value